Profile of Progesterone Levels After Administration of Gonadotropins in Dairy Cattle with Ovarian Hypofunction - Berliana, Erprinanda Galuh; Utama, Suzanita; Wurlina, Wurlina; Srianto, Pudji; Lestari, Tita Damayanti; Ratnani, Hermin (Universitas Airlangga, 2023)
This study aimed to evaluate the profile of progesterone in dairy cattle with ovarian hypofunction. A total of 10 cows in this study were evaluated three times in the collection phase, i.e. (F1) when the cow was diagnosed with ovarian hypofunction, (F2) when the cow was in heat and (F3) 21 days after artificial insemination to detect pregnancy. Samples in the form of blood serum were then analyzed using ELISA. As a result, the average time of heat in ovarian hypofunction cows was 7,4 days. Progesterone levels in F1 were 1,027 ng/ml, 2,774 ng/ml, 1,476 ng/ml, 2,256 ng/ml, 1,258 ng/ml, 1,758 ng/ml, 2,393 ng/ml, 0,592 ng/ml, 0,755 ng /ml, 1,876 ng/ml, respectively. Progesterone levels in F2 were 0,671 ng/ml, 0,517 ng/ml, 0,763 ng/ml, 0,598 ng/ml, 0,615 ng/ml, 0,537 ng/ml, 0,726 ng/ml, 0,643 ng/ml, 0,593 ng/ml, 0,975ng/ml, respectively. Progesterone levels in F3 were 15,642 ng/ml, 4,215 ng/ml, 17,327 ng/ml, 20,721 ng/ml, 5,796 ng/ml, 17,214 ng/ml, 15,815 ng/ml, 16,745 ng/ml, 4,632 ng /ml, 18,281 ng/ml, respectively. The pregnancy rate in hypofunctional cows treated with PG-600 in this study was 70%.